Advanced mobile prehospital nursing care for elderly people post-trauma: integrative review - Degani,Gláucia Costa (2019)
ABSTRACT Objective: to identify scientific evidences available on the literature on nursing interventions on advanced mobile prehospital care for elderly people post-trauma. Method: an integrative review of literature on the databases PubMed, CINAHL, and LILACS, from 2012 to 2017. Results: a sample composed by 26 studies, grouped into six thematic categories: circulation with hemorrhage control (n=11); dysfunction, neurological state (n=7); airway with protection of the cervical spine (n=3); secondary evaluation (n=3); ventilation and breathing (n=1), and environment exposition/control (n=1). Conclusion: Despite having identified nursing interventions, there was no description of specific nursing interventions related to advanced mobile prehospital care for elderly people post-trauma.